Gaining access to housing in Germany : the foreign minority experience - Anita I. Drever; William A. V. Clark (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
Housing is a critical component of household well being and the extent to which minority households have achieved parity with Germans is a measure of the extent to which this population is integrated into the larger German society. Specifically we examine whether the housing conditions for immigrants has improved between 1985 and 1998 despite the greater barriers to upward mobility for low skill workers arising from industrial restructuring. We use regression models to determine the degree to which socioeconomic differences between the two populations account for variations in the average quality of their housing. Finally, given the low number of vacancies in the German housing market and the disadvantaged position of minorities within it, we are interested in measuring the magnitude of the improvements persons of foreign origin are able to make through residential mobility. Our descriptive analyses reveal that although housing conditions for minorities have improved in absolute terms across a wide array of indicators, only in a few instances has the housing quality gap between Germans and persons of foreign origin narrowed. Further, we find that the housing conditions of minorities remained poorer even after controlling for variables thought to be strong predictors of housing quality (income, age, family size etc..) Finally, persons of foreign origin are becoming increasingly likely to move into the large, often geographically and socially isolated apartment complexes built in the post World War II era.
Keywords: 330; Wohnungsversorgung; Migranten; Ausländer; Soziale Integration; Wohnungswechsel; Deutschland